Comprehensive characterization of European house dust contaminants: Concentrations and profiles, geographical variability, and implications for chemical regulation and health risk - Peter Haglund; Nikiforos A. Alygizakis; Adrian Covaci; Lisa Melymuk; Pernilla Bohlin Nizzetto; Pawel Rostkowski; Alexandre Albinet; Sylvana Alirai; Dagny Aurich; Stefan Bieber; Ana Ballesteros-Gómez; Amanda A. Brennan; et al. (Science of The Total Environment, 2024)

Concentrations of potentially endocrine disrupting chemicals in car cabin air and dust – Effect of temperature and ventilation - Jenny Lexén; Christine Gallampois; Maria Bernander; Peter Haglund; Aleksandra Sebastian; Patrik L. Andersson (Science of The Total Environment, 2024)

Pesticide screening of surface water and soil along the Mekong River in Cambodia - Putheary Ngin; Peter Haglund; Sorya Proum; Jerker Fick (Science of The Total Environment, 2024)

Temporal trends of lipophilic organic contaminants in blue mussel (1994–2017) and eelpout (1994–2017) from the southern Baltic Sea - Andriy Rebryk; Jan Koschorreck; Peter Haglund (Science of The Total Environment, 2023)

Effects on the food-web structure and bioaccumulation patterns of organic contaminants in a climate-altered Bothnian Sea mesocosms - Åsa M. M. Berglund; Christine Gallampois; Matyas Ripszam; Henrik Larsson; Daniela A. Figueroa; Evelina Grinienė; Pär Byström; Elena Gorokhova; Peter Haglund; Agneta Andersson; Mats Tysklind (Frontiers in Marine Science, 2023)
Climate change is expected to alter global temperature and precipitation patterns resulting in complex environmental impacts. The proposed higher precipitation in northern Scandinavia would increase runoff from land, hence increase the inflow of terrestrial dissolved organic matter (tDOM) in coastal regions. This could promote heterotrophic bacterial production and shift the food web structure, by favoring the microbial food web. The altered climate is also expected to affect transport and availability of organic micropollutants (MPs), with downstream effects on exposure and accumulation in biota. This study aimed to assess climate-induced changes in a Bothnian Sea food web structure as well as bioaccumulation patterns of MPs. We performed a mesocosms-study, focusing on aquatic food webs with fish as top predator. Alongside increased temperature, mesocosm treatments included tDOM and MP addition. The tDOM addition affected nutrient availability and boosted both phytoplankton and heterotrophic bacteria in our fairly shallow mesocosms. The increased tDOM further benefitted flagellates, ciliates and mesozooplankton, while the temperature increase and MP addition had minor effect on those organism groups. Temperature, on the other hand, had a negative impact on fish growth and survival, whereas tDOM and MP addition only had minor impact on fish. Moreover, there were indications that bioaccumulation of MPs in fish either increased with tDOM addition or decreased at higher temperatures. If there was an impact on bioaccumulation, moderately lipophilic MPs (log K ow 3.6 – 4.6) were generally affected by tDOM addition and more lipophilic MPs (log K ow 3.8 to 6.4) were generally affected by increased temperature. This study suggest that both increased temperatures and addition of tDOM likely will affect bioaccumulation patterns of MPs in shallow coastal regions, albeit with counteracting effects.

mRNA Expression and Biomarker Responses in Perch at a Biomonitoring Site in the Baltic Sea – Possible Influence of Natural Brominated Chemicals - Lars Förlin; Noomi Asker; Mats Töpel; Tobias Österlund; Erik Kristiansson; Jari Parkkonen; Peter Haglund; Suzanne Faxneld; Joachim Sturve (Frontiers in Marine Science, 2019)

Atmospheric pathways of chlorinated pesticides and natural bromoanisoles in the northern Baltic Sea and its catchment - Terry Bidleman; Kathleen Agosta; Agneta Andersson; Eva Brorström-Lundén; Peter Haglund; Katarina Hansson; Hjalmar Laudon; Seth Newton; Olle Nygren; Matyas Ripszam; Mats Tysklind; Karin Wiberg (Ambio, 2015)

Projected future climate change and Baltic Sea ecosystem management - Agneta Andersson; H. E. Markus Meier; Matyas Ripszam; Owen Rowe; Johan Wikner; Peter Haglund; Kari Eilola; Catherine Legrand; Daniela Figueroa; Joanna Paczkowska; Elin Lindehoff; Mats Tysklind; et al. (Ambio, 2015)

The use of comprehensive two-dimensional gas chromatography and structure–activity modeling for screening and preliminary risk assessment of organic contaminants in soil, sediment, and surface water - Patricia Moreira Bastos; Peter Haglund (Journal of Soils and Sediments, 2012)

Brominated phenols, anisoles, and dioxins present in blue mussels from the Swedish coastline - Karin Löfstrand; Anna Malmvärn; Peter Haglund; Anders Bignert; Åke Bergman; Lillemor Asplund (Environmental Science and Pollution Research, 2010)

The internal barriers of rotation for the 209 polychlorinated biphenyls - Patrik L. Andersson; Peter Haglund; Mats Tysklind (Environmental Science and Pollution Research, 1999)

The internal barriers of rotation for the 209 polychlorinated biphenyls - Patrik L. Andersson; Peter Haglund; Mats Tysklind (Environmental Science and Pollution Research, 1997)